Med tradicionalno in permisivno seksualno kulturo - Švab, Alenka (Družboslovne razprave, 2010)
The article presents the results of qualitative research (focus groups) into perceptions of sexuality amongst female university students. The starting point was that perceptions regarding sexuality are grounded in the following key social contexts: reflexive individualism, changes in intimacy and partnership, a permissive sexual culture as the dominant one, and in traditional sexual culture as a residual sexual culture. The results highlighted three key characteristics. The first is a differential view on sexuality in general and on orgasm in particular. The second characteristic is the comprehension of sexuality in the context of partnership, while the third is autonomy and reflexive views on sexuality and partnership.
Keywords: Students; Študentje; woman; Women; Ženske; sexual intercourse; Sexuality; Spolnost; Kvalitativna analiza; Qualitative analysis; Slovenia; Slovenija; študentke; spolno vedenje; zaznavanje; družboslovno raziskovanje